Pengaruh Konseling Kelompok dengan Teknik Positive Affirmation untuk Mereduksi Rasa Insecure: Penelitian - Khairisa Aisyah Meutuwah; Mirna Ari Mulyani; Lena Marianti (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research is motivated by the phenomenon of insecurity commonly experienced by students, especially in the academic realm, which can hinder their learning potential and performance. Insecurity that is not managed properly has the potential to lead to anxiety, lack of self-confidence, and withdrawal from social environments. Therefore, this study aims to assess the effect of group counseling with positive affirmation techniques in reducing students' insecurity. This study is a quantitative study using a quasi-experimental method of the non-equivalent group design using a pretest and posttest. There were 16 students as the research sample who were then randomly divided into two groups, namely the experimental group and the control group. The results showed that before being given group counseling, BPI Batch 21 students had moderate to high levels of insecurity (mean = 107; SD = 15). After intervention using positive affirmation techniques, the level decreased significantly (mean = 38; SD = 10), with the majority of respondents moving into the low to moderate category. The paired samples t-test showed a significance value of p = 0.000 (p < 0.05), which indicates that group counseling with positive affirmation techniques had a significant effect in reducing the feeling of insecurity of BPI students of Class 21.